Relationship between Mother's Behavior Regarding Toilet Training for Toddlers at the Tenayan Raya-Riau Community Health Center - Napitupulu, Siska Mariany Ocfica (Sean Institute, 2023)
Abstract: Toilet Training is a way to train children to be able to control urination and defecation. With Toilet Training, it is hoped that children will be able to urinate and defecate in designated places. The most common impact of failure in Toilet Training is the presence of strong treatment or rules for parents towards their children which can interfere with the child's personality or tend to be stubborn. The aim of the research is to determine the relationship between maternal behavior regarding toilet training in toddlers. This type of research is analytical with a cross-sectional design using random sampling, with a sample of 32 respondents, with a total of 20 questionnaires submitted to respondents. Based on research, it was found that the relationship between mothers' behavior regarding toilet training was sufficient for 28 mothers (87.5%), and the relationship between mothers' behavior regarding the definition of toilet training was sufficient for 27 mothers (84.4%). In relation to maternal behavior regarding the right time for the child to be ready to start toilet training, 16 mothers (71.9%) were sufficient. In relation to maternal behavior, 25 mothers (68.8%) indicated that children were ready to start toilet training. Regarding the relationship between mothers' behavior regarding tips to make toilet training easier, there were 26 mothers (81.3%). Therefore, it is hoped that families, especially mothers, can improve their behavior regarding toilet training by making mothers more active in seeking information about toilet training by using existing facilities, TV, radio, and health workers. 5 %), In relation to maternal behavior regarding the definition of toilet training, 27 mothers (84.4%) were sufficient. In relation to maternal behavior regarding the right time for the child to be ready to start toilet training, 16 mothers (71.9%) were sufficient. In relation to maternal behavior, 25 mothers (68.8%) indicated that children were ready to start toilet training. Regarding the relationship between mothers' behavior regarding tips to make toilet training easier, there were 26 mothers (81.3%). Regarding the relationship between mothers' behavior regarding tips to make toilet training easier, there were 26 mothers (81.3%). Regarding the relationship between mothers' behavior regarding tips to make toilet training easier, there were 26 mothers (81.3%). Therefore, it is hoped that families, especially mothers, can improve their behavior regarding toilet training by making mothers more active in seeking information about toilet training by using existing facilities, TV, radio, and health workers.